UAV photogrammetry for archaeological site survey. 3D models at the Hierapolis in Phrygia (Turkey) - Filiberto Chiabrando; Francesco D'Andria; Giulia Sammartano; Antonia Spanò (Virtual Archaeology Review)
Unmanned aerial vehicle (UAV) photogrammetry has shown a very rapid development in many fields, especially in archaeological excavation areas and architectural complexes, where it offers a detailed generation of three-dimensional (3D) data including the possibility of updating over time. It also proves to be a very flexible tool applicable to many types of complex areas with a variety of different features. The use of aerial acquisition provides highly effective results, adding to both rapid capture and lower costs. In fact, today in the field of archaeological research, great efforts are invested in the generation of very large-scale models and orthophotos, and the technology seems to promise further future developments, not only from the terrestrial (orthogonal) point of view, but also from the nadiral direction from a low altitude, as a preferential and often optimal point of view. Here an effective workflow for photogrammetric product generation is presented for selected case studies in some monumental areas of ancient Hierapolis in Phrygia (Turkey), in which the Italian Archaeological Mission of Hierapolis (MAIER) has been working since the 1960s. The recent experiences achieved by UAV photogrammetry are quite innovative. The variety and complexity of the buildings, as well as the height of their ruins, offer numerous challenges, which are interesting to deal with. The 3D aerial survey was performed for multiple purposes with the eBee system by Sensefly. Specific attention was paid to the digital surface model (DSM) and aerial orthoimages of three test areas: the Plutonium area; the Thermal Bath-Church; and the Necropolis. Starting from the same technical approach, a comparative assesment among the three sites was carried out, taking into account the specific goals, the type of the structure and the terrain conformation.